USING GOOGLE TRANSLATE APPLICATION TO TEACH ENGLISH PRONUNCIATION - Wati, Windi Mustika; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Pronunciation is an important aspect in English language. It is important for language learner to improve their pronunciation skill in early stage such as junior high school. This study aim to help the pronunciation problems found among the junior high school student in MTsN Ngabang. By implementing preexperimental research, this study aim to find out the effectiveness of utilizing Google Translate apps to teach student pronunciation especially in vowel and consonant by. This study also measure the effect size of using Google Translate apps to teach pronunciation. The participant of this research is eight grade students of MTsN Ngabang. The data was collected through pre-test, treatment and post-test process. The students"™ achievement in increasing with the interval score of Pre-Test and Post-Test is 13,5. The significance difference of this achievement can also proved by the t-test score (3,62) is higher than t-table (2,06) at 5%. Therefore, Null Hypothesis is rejected. The research findings reveal the effectiveness of using the Google Translate application for teaching English pronunciation is high with an effect size value of 1,08.